Les médias, l’autre et moi - Marlène Loicq (Communication)
The media have deeply integrated the social and personal lives of individuals, especially the younger generations. They provide a wide range of experiences upon which to base the permanent process of identity construction. This research brief suggests that media education is a fertile ground to explore media practices, “mediacultures” and the mastery of those tools involved in the construction of one’s self and that of the other. Combining reflexive perspective and analysis, the author describes the stages of an action research project conducted on the topic of “the foreigner”.